Delimitations of the Professional Judgment within an Economic Environment - VIORICA MIRELA ȘTEFAN-DUICU; ADRIAN ȘTEFAN-DUICU (Global Economic Observer)
The professional judgment is a base concept “sine-qua-non” within a company because it displays the intrinsic attribute for performing the activity. In our accepting, bringing together the determinant factors of the professional judgment and also the universality of the component parts and the influences oriented on the professional judgment we obtain an ample professional result for which we propose the title of “spectral value of the professional judgment”. Through this paper we aim to describe the classical component of the professional judgment and also the secondary elements that we have built at a conceptual and original level starting from the base notions presented.